2016
DOI: 10.1111/ecin.12335
|View full text |Cite
|
Sign up to set email alerts
|

Labor Market Performance Effects of Discrimination and Loss of Skill

Abstract: We examine the impact of discrimination on labor market performance when workers are subject to a risk of losing skills during an unemployment experience. Within a search and matching framework, we show that both natives and immigrants are affected by discrimination. Discrimination in one sector has positive spillovers, inducing employment to increase in the other sector and the effect on labor market performance therefore depends on whether discrimination is present in only one sector or in both. Discriminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In the United States, research has established quite clearly the persistence of vulnerabilities and inequalities in employment, mobility, wages and dismissals for workers belonging to minorities, despite the existence of civil rights protection for over 50 years [21]. The impact of discrimination on immigrant workers was studied by Larsen and Waisman [22] using a search and wage-bargaining model, their results indicating high unemployment rates, lower wages, and lower productivity jobs among immigrants in the US. Wilson and Rodgers [23] analyzed the black-white earning differentials taking into account several socio-demographic control variables like age, gender, education, or residency and observed that discrimination explains an important part of the wage gap.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the United States, research has established quite clearly the persistence of vulnerabilities and inequalities in employment, mobility, wages and dismissals for workers belonging to minorities, despite the existence of civil rights protection for over 50 years [21]. The impact of discrimination on immigrant workers was studied by Larsen and Waisman [22] using a search and wage-bargaining model, their results indicating high unemployment rates, lower wages, and lower productivity jobs among immigrants in the US. Wilson and Rodgers [23] analyzed the black-white earning differentials taking into account several socio-demographic control variables like age, gender, education, or residency and observed that discrimination explains an important part of the wage gap.…”
Section: Literature Reviewmentioning
confidence: 99%